2020
DOI: 10.26505/djm.19025550828
|View full text |Cite
|
Sign up to set email alerts
|

The Role of C-Reactive Protein in the Infections Caused by Parasites(Review)

Abstract: Background: Inflammation causes a rise in the levels of certain proteins; these proteins are identified as acute stage proteins and one of these proteins is C-reactive protein (CRP). CRP composed of 206-amino acid of the short pentraxin family. Objective: This review assessed CRP as an inflammatory indicator that has an important role in the host's defense against infection and also it is documented the pivotal role of this protein during infections with different parasites. Conclusion: This review is hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(44 reference statements)
1
0
0
Order By: Relevance
“…These data are consistent with earlier reports, where CRP level increased significantly at one weeks after invasion then decreased to below normal (Hoole et al, 2003;Roy et al, 2017). Saheb et al (2020) reported that concentration of CRP elevates depending on the protozoa parasitic infection and the value can be used as a non-specific indicator of examination of the clinical presentation.…”
Section: Resultssupporting
confidence: 92%
“…These data are consistent with earlier reports, where CRP level increased significantly at one weeks after invasion then decreased to below normal (Hoole et al, 2003;Roy et al, 2017). Saheb et al (2020) reported that concentration of CRP elevates depending on the protozoa parasitic infection and the value can be used as a non-specific indicator of examination of the clinical presentation.…”
Section: Resultssupporting
confidence: 92%